Analisis Dimensi Fraktal Sinyal Elektrokardiografi - Rizki Yara Narvinda; Arif Surtono; A Amanto (Jurnal Teori dan Aplikasi Fisika, 2017)
It has been utilized a research on the fractal dimension analysis of electrocardiographic (ECG) signals. ECG signal is one example of a fractal nature, so that this signal can be calculated using fractal dimension. The purpose of this study calculates the ECG signal by using fractal dimension. Calculation of fractal dimension is processed using matlab 7.8 software with a sampling of the ECG signal on the website www.physionet.org. Fractal dimension method used is the Box-Counting. Classification of signal samples are taken, there are two types: normal and arrhythmia. The results of the dimension values obtained MIT-BIH database Normal Sinus Rhythm is 1.37; MIT-BIH database arrhythmias is 1.49; MIT-BIH database Supraventri arrhythmias is 1.44; and Cu ventricular tachyarrhythmia is 1.21. From these data it can be concluded that the classification dimension values in the range between 1-2 is in a state of cardiac arrhythmias and classification dimension values in a normal state has a value equal to one dimension.